STRATEGI PENINGKATAN PAJAK BUMI BANGUNAN (PBB) & BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN (BPHTB) PADA BADAN PENDAPATAN DAERAH KABUPATEN OGAN ILIR - Jajang Hadi; Venni Meyliani; Reca Rovyanty; Sudirman Sudirman; Dedy Franz Ferrary (MAP Program Pascasarjana Universitas Sjakhyakirti, 2022)
This research is entitled Strategies for Increasing Land and Building Tax (Pbb) & Fees for Acquiring Rights on Land and Buildings (Bphtb) at the Regional Revenue Agency of Ogan Ilir Regency, with the aim of knowing 1). The strategy undertaken by the head of the Regional Revenue Agency in increasing Land and Building Tax & Fees for Acquisition of Land and Building Rights. 2). Supporting and hindering factors in increasing land and building tax revenue & fees for the acquisition of land and building rights at the Regional Revenue Agency of Ogan Ilir Regency. The research approach used in this research is the method used in this study is a qualitative research method. The definition of qualitative research according to Nasution (1988: 5) is research that essentially observes people in the environment, interacts with them, tries to understand their language and their interpretation of their surroundings. The data required includes secondary data and primary data obtained in various ways, including: Documentation, Interview (Indept Interview), Observation. The results of the analysis are: 1). The strategy used by the Regional Revenue Agency of Banyuasin Regency in increasing Land and Building Tax & Fees for Acquisition of Land and Building Rights by using the SO strategy is Using the power to take advantage of opportunities by (1) Utilizing advances in information technology with support from various parties (government, and post offices), (2) Utilizing capable, trustworthy and responsible employees on easy terms with affordable prices and standard quality of housing. 2) Internal and external factors of the Banyuasin Regency Regional Revenue Agency can influence the increase in Land and Building Tax & Fees for Acquiring Rights on Land and Buildings.Based on the research results, several things can be recommended, namely: 1) Improving the quality and quantity of human resources and improving software to support the interests and needs of work in the field so that services to the community can run smoothly. 2). Implementing a survival strategy against existing conditions, both the quality of facilities and infrastructure as well as human resources in order to create a conducive atmosphere.